Home enteral nutrition may prevent myelosuppression of patients with nasopharyngeal carcinoma treated by concurrent chemoradiotherapy. Issue 10 (12th July 2019) - Li, Xuemei; Zhou, Jidan; Chu, Ci; You, Qian; Zhong, Renming; Rao, Zhiyong; Hu, Wen
Abstract: Background: The aim of this study is to assess the effect of home enteral nutrition (HEN) on the myelosuppression of patients with nasopharyngeal cancer (NPC) during the course of concurrent chemoradiotherapy (CCRT). Methods: A total of 18 outpatients with NPC administered oral nutritional supplementation intervention at home during the course of CCRT were designated as the HEN group, whereas 36 patients with NPC who had previously completed CCRT were retrospectively included as the control group. Patient Generated Subjective Global Assessment, body mass index (BMI), and blood test were evaluated prior to CCRT. During the course of CCRT, blood test was assessed every 2 weeks. Results: In male patients, hemoglobin (HB) and red blood cell were decreased ( P  < .05) in both HEN and control group after CCRT, whereas white blood cell (WBC) started to decrease since week 2 of CCRT in the control group but maintained in the HEN group which was significantly higher than the control (5.05 ± 1.29 vs 3.77 ± 1.5, P  < .05). In female patients, HB and WBC were reduced in control group during CCRT, whereas these indicators also maintained in the HEN group. Surprisingly, all patients with lower BMI (<24 kg/m 2 ) had a significant increase in platelet (PLT) after CCRT (200.78 ± 58.03 vs 253.00 ± 69.82, P  < .05), while had steady HB and WBC values in the HEN group. At the end of CCRT, WBC and PLT of the HEN group were both higher than those in the control group (5.21 ± 1.07 vs 3.37 ± 1.52), (253.00 ± 69.82 vs 165.57 ± 59.56) ( P  < .05 for both). Our findings suggest that HEN is effective in preventing myelosuppression during CCRT for patients with NPC. Conclusion: Our findings suggest that HEN is effective in preventing myelosuppression during CCRT for patients with NPC.